2015
DOI: 10.1111/ctr.12621
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk and mortality post‐kidney transplantation

Abstract: Fracture rates in English kidney transplant recipients are lower than previously reported in US cohorts. Sustaining a hip fracture is associated with an increased mortality risk. Our results can be used to power future fracture prevention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
9
30
0
2
Order By: Relevance
“…We hypothesized that a fracture prediction tool incorporating both general and transplant-specific risk factors may improve fracture prediction [11] . However, model updating may not be needed as the absolute fracture rate found in the current study was lower than previously reported, similar to other recently conducted studies [27,28] . Moreover, the strength of the transplant-specific risk factors was only moderate.…”
Section: Discussionsupporting
confidence: 85%
“…We hypothesized that a fracture prediction tool incorporating both general and transplant-specific risk factors may improve fracture prediction [11] . However, model updating may not be needed as the absolute fracture rate found in the current study was lower than previously reported, similar to other recently conducted studies [27,28] . Moreover, the strength of the transplant-specific risk factors was only moderate.…”
Section: Discussionsupporting
confidence: 85%
“…The mean follow‐up ranged from 1 to 10 years. We found 18 studies that evaluated the risk of fracture in KT group, without a comparator in 14 studies, compared with the general population in 3 studies and compared with dialysis population in 1 study (Table ). Concerning dialysis population (HD and PD), 5 studies reported the risk of fracture, without a comparator in 2 studies, and compared with the general population in 3 studies .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported an incidence rate of overall fracture from an administrative database compared with 9 studies from a cohort or a clinical registry. From administrative databases, the incidences of overall fracture reported in 2 HD group studies were similar to those reported in 5 KT group studies (Fig. C ).…”
Section: Resultsmentioning
confidence: 99%
“…This trend partly reflects a significant reduction in cumulative glucocorticoid (GC) exposure, but this may not account for all of the reduction in fractures (10); other factors may be important, including improved management of CKD-MBD pretransplantation and bone protection strategies, such as vitamin D and bisphosphonates in kidney transplant recipients, as well as changes in lifestyle and physical activity. Despite the reduction in hip fracture rates, outcomes after hip fracture are poor, with a recent analysis of 21,769 kidney transplant recipients in the United Kingdom indicating that a hip fracture was independently associated with a threefold increase in mortality risk (11).…”
Section: Epidemiologymentioning
confidence: 99%